Patients with NSTEMI have fewer symptoms and higher quality of life three months after admission for acute chest pain. (14th October 2021) - Saeed, N; Norekvaal, T M; Steiro, O T; Tjora, H L; Langoergen, J; Bjoerneklett, R; Skadberg, O; Bonarjee, V V S; Mjelva, O R; Omland, T; Vikenes, K; Aakre, K M; et al.
Abstract: Background: A substantial proportion of patients admitted for possible non-ST elevation acute coronary syndrome (NSTE-ACS) who are not diagnosed with non-ST elevation myocardial infarction (NSTEMI) suffer from conditions (e.g. chronic myocardial injury [CMI]) that may imply serious cardiac risk and impaired quality of life. It is unknown what predicts quality of life and recurrence of symptoms in chest pain patients. Purpose: To investigate which demographic and clinical characteristics, including discharge diagnosis, that predict recurrent symptoms and quality of life three months after hospitalization for acute chest pain. Methods: A total of 1506 patients ≥18 years admitted with suspected NSTE-ACS at Haukeland University Hospital, Bergen, Norway, were included in the WESTCOR study. The final diagnosis was adjudicated by two independent cardiologists based on all clinical data including routine cTnT (5th gen, Roche Diagnostics). Three months after discharge patients received questionnaires assessing general health (SF-12v1), angina-related health (SAQ-7) and dyspnea (Rose Dyspnea Scale). In all, 774 (51.3%) patients responded and were included in the analyses. Univariable and multivariable regression models were applied to identify predictors of symptoms and quality of life scores after adjusting for a subset of candidate predictors. A subgroup analysis was undertaken in patients with stable troponin concentrations (N=658). Results: Based on the discharge diagnosis the patients were grouped as NSTEMI (14.2%), unstable angina pectoris (UAP) (16.9%), non-coronary cardiac disease (6.6%), non-cardiac disease (6.3%) and non-cardiac chest pain (NCCP) (56.0%). After three months the NSTEMI patients had the highest quality of life scores and the lowest prevalence of symptoms (angina and dyspnea), while the inverse was true for the UAP patients (Fig 1). Revascularized patients had a better quality of life compared to those treated conservatively (P<0.001). Adjusted multivariable analysis also demonstrated that revascularization (β=0.19, P=0.002) and a diagnosis of UAP (β=−0.18, P=0.007) succeeded to predict angina frequency. Additionally, current smoking and hypertension were also associated with worse quality of life outcomes (Table 1). NCCP patients had high median prevalence of symptoms after three months, with 50% of the group reporting chest pain in the last four weeks, and 33% reporting dyspnea. In the subgroup analysis, current smoking predicted worse quality of life in all domains (all P<0.05) except SAQ7-Angina frequency. Conclusions: Three months after hospitalization for chest pain revascularized patients had better quality of life and less symptoms compared to other patient groups. A diagnosis of UAP predicted recurrent symptoms and impaired quality of life in patients, suggesting that closer monitoring should be considered in order to minimize re-hospitalization. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The study is funded by grants from the Western Norway Regional Health Authority, Haukeland and Stavanger University hospitals.